2019
DOI: 10.14283/jpad.2019.42
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Group-Based 8-Week Multicomponent Cognitive Training on Cognition, Mood and Activities of Daily Living Among Healthy Older Adults: A One-Year Follow-Up of a Randomized Controlled Trial

Abstract: ACKGROUND: Cognitive interventions have the potential to enhance cognition among healthy older adults. However, little attention has been paid to the effect of cognitive training (CT) on mood and activities of daily living (ADL). OBJECTIVES: To assess the effectiveness of a multicomponent CT using a training program of executive functions, attention, memory and visuospatial functions (TEAM-V Program) on cognition, mood and instrumental ADL. DESIGN: A randomized, single-blinded, treatment-as-usual controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Table 1 outlines the sample characteristics and methods of the six included studies [ 18 , 19 , 20 , 21 , 22 , 23 ]. Among the six articles, one was published in 2006, one in 2011, three in 2018, and one in 2020.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 outlines the sample characteristics and methods of the six included studies [ 18 , 19 , 20 , 21 , 22 , 23 ]. Among the six articles, one was published in 2006, one in 2011, three in 2018, and one in 2020.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the methodological quality evaluation, only one article met all criteria in seven areas [ 21 ]. The details of the randomization of subjects were not mentioned in three articles, and they could not be determined [ 19 , 20 , 23 ]. The concealment of the assignment order was evaluated as a high risk of bias in one article, as participants were informed of the group assigned to them [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, the approach of combining multiple intervention components may have synergistic effects. However, multi-domain intervention studies have demonstrated mixed outcomes ( 8 12 ). The 3-year French Multidomain Alzheimer Preventive Trial (MAPT) compared the effect of 3 interventions on cognitive decline ( 9 ).…”
Section: Introductionmentioning
confidence: 99%